Setting the table for policy intrapreneurship: public administrator perspectives on local food system governance. Issue 2 (3rd April 2022) - Emas, Rachel; Jones, John C.
Abstract: In communities across the U.S., there is growing awareness of food system issues which exerts greater pressure on public servants to help build a better food system for their community. Drawing from interviews with local and state-level public administrators and elected officials in two metropolitan regions in Ohio and New Jersey, and supporting interviews from food producers and nonprofit leaders in those areas, this paper examines what roles public administrators believe they could and should take regarding food system development in their community. From this qualitative data analysis, the research identified commonalities in administrators' positive and negative perceptions of the potential for development of their community's local food system (LFS) despite their lack of background knowledge regarding these systems. Given food systems' interdisciplinarity and complexity, LFS development likely requires multi-sectoral alliances via partnership governance. The alliance itself and each of its components is simultaneously a complete entity and a part of a larger, more complex entity; such entities are called holons. These alliances have greater capacity to manage more complicated problems than can be addressed by subordinate holons. In examining the potential role of local public administrators in LFS development, this paper constructs the concept of the policy intrapreneur to clarify our understanding and discussions of how public administrators, decision-makers, and other stakeholders view their roles and responsibilities in the creation and governance of local food systems.